LANGUAGE MAINTENANCE BY JAVANESE FAMILIES IN DESA SAMBIREJO TIMUR - Ayu Utatri Prastica Riadiani (LINGUISTIK TERAPAN, 2019)
This study deals with language maintenance by Javanese families. It employs qualitative research design with case study. This study aims to find out: (1) the dominant factor affect f Javanese families language maintenance in Desa Sambirejo Timur, (2) the strategies used by Javanese families to maintain their ethnic language, and (3) the reason Javanese families maintained their language. The subjects were ten Javanese families including parents (the third generation) and children in Desa Sambirejo Timur. The instruments used for this study were observation and interview (in-depth interview). The observation was applied to get the data about the factor affect Javanese families’ language maintenance. The interview was applied to find the dominant factor affect language maintenance by Javanese families. The data was analyzed by using interactive model from Miles and Huberman’s. There are five factors being analyzed, namely: (1) attitude towards Javanese language, (2)value, (3) identity, (4) demography, and social factor. The dominant factor affect Javanese lang8uage maintenance in this study is the attitude towards language. Besides that there is one additional factor found during research namely visiting homeland. The strategy used by parents to maintained Javanese language in their family are: (1) raising Javanese language interest for children by direct them to arts, culture and literature about Javanese such as wayang, Javanese radio broadcasting, and Javanese song and (2) mix Javanese language with Indonesian when speaking to the children. Key Words     : language maintenance, language attitude, family language maintenance, factors in language maintenance